A facile polymer mediated dye incorporation method for fluorescence encoded microbeads with large encoding capacities. Issue 37 (13th April 2021) - Masoomi, Hajar; Wang, Yao; Chen, Cang; Zhang, Jiayu; Ge, Yunfei; Guo, Qingsheng; Gu, Hongchen; Xu, Hong
Abstract : A facile and universal dye incorporation method for fluorescence encoded microbeads via the polymer mediated approach is proposed. Abstract : Here we report a facile dye incorporation method for fluorescence encoded microbeads, which is achieved by tuning the mixed polymer type (blank and dye-labeled polymers) and their doping ratio through electrostatic loading into mesoporous beads. This method is universal to various carriers and could render large encoding capacities.